Synthesis, Characterization, and Pharmacological Evaluation of Metal-Chelating Compounds for Neuroprotection in Oxidative Stress-Induced Neuronal Damage (Cuestiones de Fisioterapia, 2025)
Neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) are associated with oxidative stress and metal ion dysregulation, leading to neuronal damage. Excessive accumulation of metal ions such as Fe³⁺, Cu²⁺, and Zn²⁺ catalyzes reactive oxygen species (ROS) generation, exacerbating neuronal apoptosis. Metal-chelating compounds have emerged as potentialneuroprotective agents by regulating metal homeostasis and reducing oxidative stress.